Analysis of Islamic Learning at Homeschooling: Analisis Pembalajaran PAI di Homeschooling - Sofia Annajah Syamsi; Imam Fauji (Universitas Muhammadiyah Sidoarjo, 2022)
This study aims to determine the PAI learning process at Homeschooling Al-Ma'mun Hanif Arsyad starting from the lesson planning to the evaluation used in PAI learning at Homeschooling Al-Ma'mun Hanf Arsyad. Considering today's adults, homeschooling has become one of the alternative schools that are in demand to replace formal schools. This research is a qualitative research. The subjects in this study were PAI learning teachers at Homeschooling Al-Ma'mun Hanif Arsyad and the principal or head of the foundation. The research method used in this research are interviews, observation and documentation. The data analysis technique in this study is descriptive qualitative, the results are described in words so as to produce a conclusion. The result is that learning planning at Homeschooling Al-Ma'mun Hanif Arsyad is carried out at the beginning of each new academic year, compiled together with the homeschooling administrator. The PAI learning process at Homeschooling Al-Ma'mun Hanif Arsyad where for PAI learning students are required to follow while for general learning students are free to choose which learning students want to follow after going through a discussion process between teachers, parents and students. While the evaluation of PAI learning at Homeschooling Al-Ma'mun Habif Arsyad is carried out every mid and end of the semester in collaboration with the National Education Office, but the social issues are adjusted to the homeschooling manhaj. The advantage of PAI learning at Homeschooling Al-Ma'mun Hanif Arsyad lies in the curriculum that is applied, where they apply 75% of the diniyah curriculum and 25% of the education curriculum.